Favorable Hemocompatibility in HeartMate 3 May Prevent Thrombosis After Prolonged Pump Cessation. Issue 2 (22nd March 2021) - Rohm, Charlene; Howard, Brian; Lakhani, Baqir; Luu, Theresa; Snipelisky, David
Abstract : The HeartMate 3 Left Ventricular Assist System has demonstrated a reduction in risk of pump thrombosis. The improved hemocompatibility of this device is largely attributed to the pump mechanics including a large-diameter outflow graft, increased retrograde flow through the pump during pump cessation, and the textured blood-contacting surfaces of the pump. We present a 55-year-old man with a HeartMate 3 device who presented with heart failure symptoms, prolonged pump cessation for 7 days, and subtherapeutic anticoagulation therapy. Despite prolonged pump cessation and interrupted anticoagulation therapy, there was no evidence of pump thrombosis as determined by both laboratory and imaging studies. This case suggests favorable hemocompatibility of the HeartMate 3 device, which clinicians may consider in the management of patients needing advanced therapies.